On Two-Period Committee Voting: Why Straw Polls Should Have Consequences - Tim Frommeyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We consider a committee voting setup with two rounds of voting where committee members, who possess private information about the state of the world, have to make a binary decision. We investigate incentives for truthful revelation of their information in the first voting period. Coughlan (2000 shows that members reveal their information in a straw poll only if their preferences are homogeneous. By taking costs of time into account, we demonstrate that heterogeneous committees have strictly higher incentives to reveal information and can be strictly better off if the straw poll allows for an earlier decision for high level of consensus.
Keywords: D72; D82; D83; 330